2019
DOI: 10.1080/17461391.2019.1587521
|View full text |Cite
|
Sign up to set email alerts
|

Upper‐body repeated‐sprint training in hypoxia in international rugby union players

Abstract: This study investigated the effects of upper-body repeated-sprint training in hypoxia vs. in normoxia on world-level male rugby union players' repeated-sprint ability (RSA) during an international competition period. Thirty-six players belonging to an international rugby union male national team performed over a 2-week period four sessions of double poling repeated-sprints (consisting of 3 × eight 10-s sprints with 20-s passive recovery) either in normobaric hypoxia (RSH, simulated altitude 3000 m, n = 18) or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
6
1
Order By: Relevance
“…Additionally, the increased changes in blood perfusion due to the combination of high-intensity and hypoxic stress may be a stimulus for altering vascular blood flow regulation due to neural, metabolic, and mechanical influences. Of interest is that short blocks (i.e., as little as 4–8 repeated sprint training sessions in hypoxia), led to improved performance for elite athletes in different sports as cycling (Faiss et al, 2013), cross-country skiing (Faiss et al, 2014), rugby (Beard et al, 2018, 2019), and tennis (Brechbuhl et al, 2018). To our knowledge, there is no data available on the effects of such exercises in astronauts and other participants during spaceflights but one may speculate that performing high-intensity exercise training in hypoxia may be a valuable and practical method for exercise countermeasure during spaceflight missions.…”
Section: High-intensity Exercise With Systemic Hypoxiamentioning
confidence: 99%
“…Additionally, the increased changes in blood perfusion due to the combination of high-intensity and hypoxic stress may be a stimulus for altering vascular blood flow regulation due to neural, metabolic, and mechanical influences. Of interest is that short blocks (i.e., as little as 4–8 repeated sprint training sessions in hypoxia), led to improved performance for elite athletes in different sports as cycling (Faiss et al, 2013), cross-country skiing (Faiss et al, 2014), rugby (Beard et al, 2018, 2019), and tennis (Brechbuhl et al, 2018). To our knowledge, there is no data available on the effects of such exercises in astronauts and other participants during spaceflights but one may speculate that performing high-intensity exercise training in hypoxia may be a valuable and practical method for exercise countermeasure during spaceflight missions.…”
Section: High-intensity Exercise With Systemic Hypoxiamentioning
confidence: 99%
“…combination of stressors, heat stress, hypoxia, repeated-sprints training in normoxia (Beard, Ashby, Kilgallon, Brocherie, & Millet, 2019;Brocherie, Girard, Faiss, & Millet, 2017;Kasai et al, 2015). Such larger hypoxia-induced performance improvements could be mediated by the physiological adaptations that arise from this training, including increased anaerobic glycolysis (Bowtell, Cooke, Turner, Mileva, & Sumners, 2014;Ogura, Katamoto, Uchimaru, Takahashi, & Naito, 2006) and muscle blood perfusion (Faiss et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…4 Moreover, several authors have reported greater performance enhancement when RSH was performed with arms than with legs: cycling vs double poling in endurance athletes 4,10 or in elite rugby players. 11,12 Therefore, the purpose of this study was to examine the vascular and oxygenation responses to acute repeated sprint arm cycling with conditions of systemic hypoxia, BFR, as well as in combination. It was hypothesized (1) that repeated sprint arm cycling performance would have greater performance impairment with systemic hypoxia, BFR, and the combination due to limited convective oxygen delivery and greater vascular resistance; (2) that greater changes in total hemoglobin would be elicited during sprints as the severity of systemic hypoxia and BFR increased; (3) that BFR alone and in combination with systemic hypoxia would elicit greater changes in total hemoglobin than systemic hypoxia alone due to different vascular mechanisms, which may decrease with duration of sprints due to fatigue and limited oxygen utilization near exhaustion.…”
Section: Introductionmentioning
confidence: 99%